Hubungan Antara Keharmonisan Keluarga dan Konformitas Teman Sebaya dengan Penyesuaian Diri Siswa di MTs Yayasan Pendidikan Agama Islam - Badan Koordinasi Agama Islam (YAPI-BKAI) Sei Karang Galang - Maimunah, Siti; Lubis, Syaiful Akhyar; Hardjo, Suryani (Mahesa Research Center, 2023)
This study aims to look at the correlation between family harmony and peer conformity with students' self-adjustment. The hypothesis put forward: there is a positive correlation between family harmony and peer conformity with student self-adjustment at MTs YAPI Sei Karang Galang. This means that the higher the family harmony and peer conformity, the better the student's self-adjustment. The population in this study were all students of MTs YAPI-BKAI Sei Karang Galang, totaling 345 students and the research sample was students of class VII MTs, totaling 160 students. The data collection method uses a quantitative method with a Likert scale, namely the family harmony scale, peer conformity scale and self-adjustment scale. The results of the analysis using multiple linear regression analysis method, it is known that there is a significant positive correlation between family harmony and peer conformity with students' self-adjustment seen from the value of the determinant coefficient (Rxy) = 0.631 with p = 0.000 <0.050. The contribution made by the variables of family harmony and peer conformity to student self-adjustment is R2 = 0.398. This means that the correlation between family harmony and peer conformity contributes to student self-adjustment by 39.8%. The remaining 60.2% is the influence of other factors. The class VII students of MTs YAPI Sei Karang Galang turned out to have moderate family harmony, peer conformity was in the medium category, while in terms of self-adjustment it was classified in the low category.